Perancangan Komunikasi Visual keraton Sumenep Melalui Buku Fotografi Sebagai Upaya Mengenalkan Peninggalan Sejarah - Firmansyah, Rahmat Aulia; Budiardjo, Hardman; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
This research deals with the design of the Keraton Sumenep visual communic ation through photography books to introduce the historical heritage. The background that makes Keraton Sumenep as the main focus in this research because the Keraton Sumenep is one of the accessible historical tourism place in the city. But there are many people who do not recognize the Keraton Sumenep                Keraton Sumenep photography book design aims to introduce the Keraton Sumenep to public because nobody has recognized it yet. Because this is an asset that we should recognize. The book is well choosen as a media to stimulate people’s emotional feeling and it can be printed regularly.                In the study, the researcher applied the qualitative approach and they obtained the information from interviews, literatur studies, observation, documentation, and competitors. Qualitative research design has flexible and changeable nature of appropriate condition in the field. These data was taken from Keraton Sumenep during study.                By the existence, it could produce a book of photography of the Keraton Sumenep that contains photographs of the area and the building of the Keraton Sumenep, the valuable goods and its annual event. Keraton Sumenep is expected to become historical sights that are widely known and widely visited by tourist. Keywords: Design, Photography Books, Keraton Sumenep